(untitled) (The Pakistan Development Review, 1989)
The central message of Keynesian economics is that demand management through monetary and fiscal policies can successfully stabilize output and employment in the short run, and possibly raise the average level of employment over a longer period. The Monetarists, on the other hand, have emphasized the role of monetary policy in stabilizing output and employment in the short run but have maintained that money is neutral in the long run. The rational expectations literature seeks to explain to what extent Keynesian and Monetarist nominal demand policies can have real effects, even in the short run, when allowance is made for rational behaviour and some short-term nominal rigidities. It is generally contended that stabilization policies would have no real effects if the principles of such policies are known to private agents, that the policies are based on information that is available to the private agents as much as to the policy-maker, and the private agents interpret information available to them correctly. The argument of rational expectations theory has been that, for demand policies to be effective, in the short run, there must be some, element of surprise and in the longer-run, all relevant in forma tion is not used. This paper uses the nalytical framework provided by Barro (1977) for the U.S. to empirically test the following two interrelated propositions about the scope of monetary policy in the case of Pakistan as put forth by the rational expectations theory: (a) The growth of the money supply is predictable in that it differs from a random walk with trend, and (b) that the unpredictable part of money supply growth will affect real output. While the primary focus is on the output effects of monetary policy, we test related propositions for fiscal policy, and as will become evident later, perhaps in a cursory fashion.